Evaluating the Use of Alternative Normalization Approaches on SARS-CoV-2 Concentrations in Wastewater: Experiences from Two Catchments in Northern Sweden - Frida Isaksson; Lian Lundy; Annelie Hedström; Anna J. Székely; Nahla Mohamed (Environments, 2022)
The detection of SARS-CoV-2 RNA fragments in feces has paved the way for wastewater-based epidemiology to contribute to COVID-19 mitigation measures, with its use in a public health context still under development. As a way to facilitate data comparison, this paper explores the impact of using alternative normalization approaches (wastewater treatment plant (WWTP) flow, population size estimates (derived using total nitrogen (TN), total phosphorus (TP) and census data) and pepper mild mottle virus (PMMoV)) on the relationship between viral wastewater data and clinical case numbers. Influent wastewater samples were collected at two WWTPs in Luleå, northern Sweden, between January and March 2021. TN and TP were determined upon sample collection, with RNA analysis undertaken on samples after one freeze–thaw cycle. The strength of the correlation between normalization approaches and clinical cases differed between WWTPs (r ≤ 0.73 or r ≥ 0.78 at the larger WWTP and r ≤ 0.23 or r ≥ 0.43 at the smaller WWTP), indicating that the use of wastewater as an epidemiological tool is context-dependent. Depending on the normalization approach utilized, time-shifted analyses imply that wastewater data on SARS-CoV-2 RNA pre-dated a rise in clinical cases by 0–2 and 5–8 days, for the lager and smaller WWTPs, respectively. SARS-CoV-2 viral loads normalized to the population or PMMoV better reflect the number of clinical cases when comparing wastewater data between sewer catchments.